2021
DOI: 10.3390/su13126898
|View full text |Cite
|
Sign up to set email alerts
|

Examining Land Use/Land Cover Change and Its Prediction Based on a Multilayer Perceptron Markov Approach in the Luki Biosphere Reserve, Democratic Republic of Congo

Abstract: Villages within the Luki Biosphere Reserve and the surrounding cities have undergone rapid demographic growth and urbanization that have impacted the reserve’s natural landscape. However, no study has focused on the spatiotemporal analysis of its land use/land cover. The present research aims at providing a comprehensive analysis of land use/land cover change in the Luki Biosphere Reserve from the year 1987 to 2020, and to predict its future change for the year 2038. Landsat images were classified in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 81 publications
2
13
0
5
Order By: Relevance
“…The primary forest has lost 13.7% (Landsat) and 13.6% (MODIS) of its area essentially to the benefit of the secondary forest. The same result has been obtained by Michel et al (2021) in the Luki BR where he founded the decreasing of 13.26% for the primary forest from 1987 to 2002 considering only the LBR extent. The same trend was observed by Potapov et al (2012) who found an increase in gross forest cover loss of 13.8% between the period 2000-2010 in DR Congo.…”
Section: Lulc Change Assessmentsupporting
confidence: 81%
See 3 more Smart Citations
“…The primary forest has lost 13.7% (Landsat) and 13.6% (MODIS) of its area essentially to the benefit of the secondary forest. The same result has been obtained by Michel et al (2021) in the Luki BR where he founded the decreasing of 13.26% for the primary forest from 1987 to 2002 considering only the LBR extent. The same trend was observed by Potapov et al (2012) who found an increase in gross forest cover loss of 13.8% between the period 2000-2010 in DR Congo.…”
Section: Lulc Change Assessmentsupporting
confidence: 81%
“…The secondary forest recorded the greatest gain in surface followed by the anthropogenic zones that gained surface area both for Landsat and MODIS images but at various rates. The results found by Michel et al (2021) showed a decrease in the secondary forest class as this was considered separately from the fields and fallows. The fallow crop and built-up areas gained surface area significantly.…”
Section: Lulc Change Assessmentmentioning
confidence: 86%
See 2 more Smart Citations
“…Multilayer perceptron with multiple hidden layers is a deep learning structure. These three kinds of deep neural networks are applied in different fields and technologies [ 11 ]. The combination of the genetic algorithm and multilayer perceptron neural network is a hybrid method of DL and the metaheuristic algorithm [ 12 ].…”
Section: Introductionmentioning
confidence: 99%